Exposure matters: Forest dynamics reveal an early Holocene conifer refugium on a north facing slope in Central Europe. (December 2020) - Pató, Zsuzsanna Anna; Standovár, Tibor; Gałka, Mariusz; Jakab, Gusztáv; Molnár, Mihály; Szmorad, Ferenc; Magyari, Enikő
Although several studies provide a broad overview of vegetation changes in the Carpathian Basin during the Holocene, stand-scale vegetation changes are lesser known because of the rarity of suitable sampling sites. In this study we investigated the sediment of a small closed-canopy site (Nagy-forrás forest hollow, 685 m a.s.l., 0.1 ha), located in the Mátra Mountains, on the north facing slope of Kékes (1014 m a.s.l.). We carried out detailed pollen, conifer stomata and plant macrofossil analyses, as well as radiocarbon dating to examine Late Glacial and Holocene dynamics of vegetation development. The site dates back to ca. 15, 500 cal yr BP, when open boreal forests and wet tundra-like habitats occurred around the hollow. Closed forest cover developed around 14, 600 cal yr BP, when a boreal European larch-Swiss stone pine ( Larix decidua-Pinus cembra ) forest surrounded the hollow. This vegetation type remained stable up to 7700 cal yr BP. We observed a hiatus between 7700 and 2710 cal yr BP, followed by a beech ( Fagus sylvatica ) dominated mixed temperate deciduous forest. Our results confirmed that the area was covered by a primary forest, as human influence was visible only from 175 cal yr BP. The relatively long lasting persistence of Pinus cembra in the Holocene at relatively low altitude was documented, which has never been found in Holocene sediments in the Pre-Carpathians before. We hypothesize that the north facing slope acted as a cold-stage refugium in the Early Holocene and could play the same role for the present-day beech forest that is threatened by recent climate change.